PENGARUH COST OF DEBT, CREDIT RATING, DAN LEVERAGE TERHADAP INCOME SMOOTHING - DWI ISROYATI, KURNIA (Jurnal Akuntansi AKUNESA, 2018)
This study aims to explain and analyze the effect of cost of debt, credit rating, and leverage towards income smoothing on non-financial companies in Indonesia that have been listed on IDX. Cost of debt is measured using the average of interest paid formula, credit rating measurement used a numeric code which is taken based on the bond rating, while leverage is measured using total debt to equity ratio, then the Jones model is used to measure income smoothing. This study uses 93 data from 31 bond issuing companies during the 2014-2016 research period. Data were analyzed using multiple linear regression method. The study found that cost of debt and credit rating have positive effect on income smoothing, while leverage has no effecton income smoothing.Keywords: EarningsManagement, IncomeSmoothing,CostofDebt, CreditRating, Leverage